A framework for precision conventional strike in post-Cold War military strategy - Birkler, J. L., 1944-; Hura, Myron, 1943-; Shlapak, David A.; Frelinger, Dave.; McLeod, Gary, 1948-; Kent, Glenn A., 1915-; Matsumura, John.; Chiesa, James, 1949-; Davis, Bruce; National Defense Research Institute (U.S.); Rand Corporation; United States. Commission on Roles and Missions of the Armed Forces (Santa Monica, CA : RAND, 1996)
Precision conventional strike (PCS) is the practice of attacking selected targets with sufficient accuracy for high probability of kill and low collateral damage. Today's PCS weapons were developed for the primary purpose of fighting a major war against the Soviet Union. What value do they have in future military strategies? The answer to this question will help to shape the roles of these weapons in future U.S. military campaigns and will have a bearing on whether some campaigns may even be undertaken. This report identifies key objectives to which PCS weapons may contribute, assesses the applicability of currently available and programmed PCS weapons across four scenarios, and suggests priorities for future acquisition and development of PCS weapons. Existing weapons provide fairly robust capabilities against soft and semihardened fixed structures, stationary mobile targets, and some targets moving with predictable direction and speed. However, their effectiveness may be limited by weather, by availability of intelligence on targets and on routes to targets, and by enemy countermeasures such as navigation signal jamming; and, where terminal air defenses have not been suppressed and air superiority has not been established, existing weapons cannot be effectively delivered against hardened targets and armor unless stealth aircraft are employed. As a result of these limitations, PCS weapons today cannot always make major contributions to achieving campaign objectives as diverse as suppressing war-supporting infrastructure and halting invading armies. The authors drew the following two inferences about investment of system development and acquisition dollars: (1) Over the near term, system development dollars should be directed toward alleviating the limitations of weather, intelligence support, and jamming; (2) progress on new antitank weapons should be carefully monitored, because such weapons could contribute mightily to the campaign objective of halting advancing armies, and sufficient numbers should be procured as a matter of high priority.
Introduction -- The Role of Precision Strike in Future Campaign Strategy -- Evolution in Technology and Operations: Potential and Limits -- A Different Approach to System Acquisition -- Appendix A: Campaign Objectives, Operational Objectives, and Tasks -- Appendix B: Intelligence Support and Mission-Planning Requirements for Precision Conventional Strike -- Appendix C: Supplement on New Technologies and Concepts of Operation.
"RAND National Defense Research Institute."
Includes bibliographical references (p. 81).
Also available on the internet via WWW in PDF format.
Keywords: Precision guided munitions -- United States; World politics -- 1989-